A new sheet die design methodology to eliminate scrap shedding problems during mass production - (:unkn) unknown (My University, 2010)
Manufacturing companies need to improve their production technology with improved dimensional accuracy at lower cost in order to manufacture sheet metal based products. Scrap shedding is an issue that should be examined at the cutting and sheet metal forming operations. In order to extend the life cycle of the cutting moulds, scrap shedding should be identified. When scrap shedding has not been taken into consideration, scraps have accumulated in the moulds reducing the production quality and causing deformation of the mould, increasing the production cost by obligating to perform extra transactions. This study becomes more focused upon the analysis of scrap shedding. In order to simulate the scrap shedding LS-Dyna and Pam Stamp software have been used. For examining of the scrap shedding an automotive part was chosen. In order to realize scrap shedding having any problems, new improvements have been suggested. Design of Experiments techniques which provide important advantages to engineering studies have been examined. By means of experimental design techniques the scrap shedding design process was also added to the classical mold design approach via a less quantities of simulations. © 2010 by ASME.